2015
DOI: 10.1371/journal.pone.0123336
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Profiling of Dystrophic Dog Muscle after MuStem Cell Transplantation

Abstract: BackgroundSeveral adult stem cell populations exhibit myogenic regenerative potential, thus representing attractive candidates for therapeutic approaches of neuromuscular diseases such as Duchenne Muscular Dystrophy (DMD). We have recently shown that systemic delivery of MuStem cells, skeletal muscle-resident stem cells isolated in healthy dog, generates the remodelling of muscle tissue and gives rise to striking clinical benefits in Golden Retriever Muscular Dystrophy (GRMD) dog. This global effect, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 84 publications
4
19
0
Order By: Relevance
“…Multilevel analyses simultaneously investigate the transcriptome and the proteome of the tissue, and thus have greater potential for providing information on the biological pathways impacted by cell therapy. However, it is noteworthy that, among the 25 proteins overexpressed following cell transplantation, only ITIH4 was identified in our previous transcriptomic study, where it was also shown to be overexpressed [10]. Similarly, among the 46 proteins identified as underexpressed, only MYH2, MYH4, and MYH7 were identified at a transcriptomic level, and were conversely shown to be overexpressed.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Multilevel analyses simultaneously investigate the transcriptome and the proteome of the tissue, and thus have greater potential for providing information on the biological pathways impacted by cell therapy. However, it is noteworthy that, among the 25 proteins overexpressed following cell transplantation, only ITIH4 was identified in our previous transcriptomic study, where it was also shown to be overexpressed [10]. Similarly, among the 46 proteins identified as underexpressed, only MYH2, MYH4, and MYH7 were identified at a transcriptomic level, and were conversely shown to be overexpressed.…”
Section: Discussionmentioning
confidence: 74%
“…MuStem cell delivery is associated with an upregulation of genes playing a role in the enhancement of skeletal muscle fiber regeneration. Simultaneously, we observed an overrepresentation of ubiquitin‐mediated protein reflecting a more active degradation process of the damaged tissue .…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Effective normalization requires appropriate reference genes, and indeed efforts to identify, validate and publicize such genes are becoming more common in a variety of disease states [20][21][22][23][24] and model organisms [25][26][27][28][29][30]. A review of the literature specifically within the DMD field however reveals a considerable number of candidates: selected examples in dystrophic dogs include GAPDH [31][32][33], RPS18 [34], HPRT1 [35,36], 18S [37]; in humans, TBP and GUSB [13]; and in mice GAPDH [33,38], ActB [39], 18S [40]. There appears to be minimal effort to apply reference genes consistently between studies (even varying from manuscript to manuscript within a research group), and data supporting the selection of the gene or genes used is rarely presented.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, we have isolated delayed adherent MDSCs from healthy dogs, which we have named MuStem cells, and demonstrated that their vascular delivery into GRMD dogs submitted to IS that started 1 week before cell administration and then maintained throughout the experiment (mentioned then as continuous IS) produce striking clinical stabilization and long-term muscle repair 58 , 59 . In the present study, we sought to determine the optimal immunosuppressive regimen required to obtain beneficial effects using the aforementioned allogeneic MuStem cells infusion protocol.…”
Section: Introductionmentioning
confidence: 99%